Implementation of ultrafast X‐ray diffraction at the 1W2B wiggler beamline of Beijing Synchrotron Radiation Facility. (14th April 2016) - Sun, Da-Rui; Xu, Guang-Lei; Zhang, Bing-Bing; Du, Xue-Yan; Wang, Hao; Li, Qiu-Ju; Zhou, Yang-Fan; Li, Zhen-Jie; Zhang, Yan; He, Jun; Yue, Jun-Hui; Lei, Ge; et al.
Abstract : A laser pump/X‐ray probe system has been established for picosecond resolution X‐ray diffraction detection at wiggler beamline 1W2B at the BSRF parasitic lightsource. Abstract : The implementation of a laser pump/X‐ray probe scheme for performing picosecond‐resolution X‐ray diffraction at the 1W2B wiggler beamline at Beijing Synchrotron Radiation Facility is reported. With the hybrid fill pattern in top‐up mode, a pixel array X‐ray detector was optimized to gate out the signal from the singlet bunch with interval 85 ns from the bunch train. The singlet pulse intensity is ∼2.5 × 10 6 photons pulse −1 at 10 keV. The laser pulse is synchronized to this singlet bunch at a 1 kHz repetition rate. A polycapillary X‐ray lens was used for secondary focusing to obtain a 72 µm (FWHM) X‐ray spot. Transient photo‐induced strain in BiFeO3 film was observed at a ∼150 ps time resolution for demonstration.